2017
DOI: 10.21767/2573-5365.100028
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Uropathogens in Urinary Tract Infection and Antibiotic Susceptibility Pattern in Riyadh Hospital, Saudi Arabia

Abstract: Background: Urinary tract infection (UTI) is one of the commonest infections encountered by clinicians and despite the widespread availability of antimicrobial agents. UTI has become difficult to treat because of appearance of pathogens with increasing resistance to antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
5
14
1
Order By: Relevance
“…Among the 100 urine samples collected in this study, 76 (76%) belonged to female population while 24 (24%) belonged to male patients. The gender distribution of patients in our study is consistent with many previous local [ 35 , 36 ] and international [ 37 , 38 ] reports showing the high incidence of UTI in women compared to men across all age groups. It has been demonstrated that the high UTI incidence in women can be attributed to many reasons such as anatomical factors that allow quick access of bacteria to the bladder, poor hygiene, sexual activity, and use of contraceptives [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among the 100 urine samples collected in this study, 76 (76%) belonged to female population while 24 (24%) belonged to male patients. The gender distribution of patients in our study is consistent with many previous local [ 35 , 36 ] and international [ 37 , 38 ] reports showing the high incidence of UTI in women compared to men across all age groups. It has been demonstrated that the high UTI incidence in women can be attributed to many reasons such as anatomical factors that allow quick access of bacteria to the bladder, poor hygiene, sexual activity, and use of contraceptives [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Recently, the level of ExPEC resistance to cephalosporins has increased markedly. For example, Al-Mijalli has reported that about 99 % of the all tested E. coli isolates were resistant to cefalotin, ceftriaxone, cefuroxime and ceftazidime, while resistance to cefoxitin and cefepime was reported in 14 and 96.7 % of isolates, respectively [14]. Another report has demonstrated that ESBL-producing UPEC isolates were associated with complete resistance to cefotaxime, ceftazidime and cefepime, and it also showed that 70.3% of these isolates were cefoxitin-resistant [9] (Table 1).…”
Section: Cephalosporinsmentioning
confidence: 99%
“…However, the level of ExPEC resistance to aztreonam has recently increased. For instance, it has been found that 74.4% of ESBL-producing UPEC isolates were aztreonam-resistant [14] ( Table 1). Another study has demonstrated that all tested ESBL-producing UPEC isolates were aztreonam-resistant, while aztreonam resistance remained very low among non-ESBL-producing ExPEC isolates and it was only detected in 1.65% of the tested isolates [9].…”
Section: Monobactamsmentioning
confidence: 99%
See 2 more Smart Citations